Antimicrobial susceptibility of propionibacterium acnes isolates from acne patients in Colombia (2013)
The increasing prevalence of antimicrobial resistance in Propionibacterium acnes poses a significant challenge to successful treatment outcomes in acne patients. Although P. acnes resistance has been demonstrated throughout the world, no previous data regarding the antimicrobial susceptibility of P. acnes in Colombia are available. The aim of this study was to determine the antimicrobial susceptibility of P. acnes to common antibiotics used in the treatment of acne in a Colombian population. Samples were collected from facial acne lesions of 100 dermatology patients. All samples were cultured in anaerobic conditions, and final identification of isolates was performed. Isolates of P. acnes were then subjected to antimicrobial susceptibility tests using erythromycin, clindamycin, tetracycline, doxycycline, and minocycline. Propionibacterium acnes isolates resistant to erythromycin (35%), clindamycin (15%), doxycycline (9%), tetracycline (8%), and minocycline (1%) were observed. Isolates with cross‐resistance were also observed (to erythromycin and clindamycin [12%] and to doxycycline and tetracycline [6%]). Overall, 46% of isolates taken from patients with a history of antibiotic use demonstrated resistance, whereas 29% of isolates taken from patients who had never used antibiotics demonstrated resistance. Antimicrobial resistance in P. acnes in this Colombian population has a lower prevalence than those reported in Europe and follows a similar pattern to findings elsewhere in Latin America. Resistance is demonstrated even in isolates from patients with no previous history of antibiotic use. Resistance to erythromycin is most commonly observed. Minocycline emerges as the most effective antibiotic.